From Sadat to Saddam : The Decline of American Diplomacy in the Middle East - Dunford, David J. (Book collections on Project MUSE., 2019)
From Sadat to Saddam: The Decline of American Diplomacy in the Middle East is a first-hand account of 30 years in the diplomatic trenches of US Middle East policy. The work reveals that the decline of U.S. diplomatic effectiveness well predates the arrival of the Trump administration.